High‐Capacity Cathode Material with High Voltage for Li‐Ion Batteries - Shi, Ji‐Lei; Xiao, Dong‐Dong; Ge, Mingyuan; Yu, Xiqian; Chu, Yong; Huang, Xiaojing; Zhang, Xu‐Dong; Yin, Ya‐Xia; Yang, Xiao‐Qing; Guo, Yu‐Guo; Gu, Lin; Wan, Li‐Jun (Advanced materials (Weinheim), 2018)
Electrochemical energy storage devices with a high energy density are an important technology in modern society, especially for electric vehicles. The most effective approach to improve the energy density of batteries is to search for high‐capacity electrode materials. According to the concept of energy quality, a high‐voltage battery delivers a highly useful energy, thus providing a new insight to improve energy density. Based on this concept, a novel and successful strategy to increase the energy density and energy quality by increasing the discharge voltage of cathode materials and preserving high capacity is proposed. The proposal is realized in high‐capacity Li‐rich cathode materials. The average discharge voltage is increased from 3.5 to 3.8 V by increasing the nickel content and applying a simple after‐treatment, and the specific energy is improved from 912 to 1033 Wh kg−1. The current work provides an insightful universal principle for developing, designing, and screening electrode materials for high energy density and energy quality. Li‐ion batteries with high energy quality require a high capacity coupled with high operating voltage. This requires the electrode materials to not only have a high specific capacity but also a high discharge voltage for cathode materials and low charge voltage for anode materials.